Analisis Penyebab Kelelahan kerja (Fatigue) Operator Dump Truck Pada Proses Coal Getting Di Wilayah Kerja Pt Bara Energi Lestari - Tiara Maulida; Zakiyuddin Zakiyuddin; T.M. Rafsanjani; Fakhrurradhi Luthfi; Jun Musnadi Is (Universitas Pahlawan Tuanku Tambusai, 2026)
The mining industry is a sector with a high level of occupational safety risk. One of the factors that can increase the risk of workplace accidents is work fatigue, as it may reduce the concentration, alertness, and productivity of heavy equipment operators. At PT Bara Energi Lestari, the coal getting process utilizes dump trucks equipped with a Driver Monitoring System (DMS) integrated into dashcams to monitor operators’ conditions. Based on preliminary monitoring conducted by the Health, Safety, and Environment (HSE) department using this system, several operators exhibited signs of fatigue, such as repeated yawning and prolonged eye closure for several seconds. These conditions may increase the risk of occupational accidents, highlighting the need to identify the factors contributing to work fatigue among dump truck operators. This study aimed to analyze the factors causing work fatigue among dump truck operators during the coal getting process in the working area of PT Bara Energi Lestari. A qualitative study with a descriptive approach was employed to gain an in-depth understanding of the causes of work fatigue among dump truck operators. Informants were selected using a purposive sampling technique, involving five participants. Data were collected through observations and in-depth interviews. The findings identified several major factors contributing to operator fatigue, including internal factors (4–6 hours of sleep duration, low back pain, and consumption of carbohydrate-rich snacks) and external factors (extreme working environment, night shifts, travel distance, and workload). The dashcam monitoring system was considered highly effective as a company control measure. Operator fatigue resulted from the interaction of poor sleep quality due to night shifts, musculoskeletal complaints, carbohydrate consumption patterns, exposure to extreme working environments, workload, uneven haul roads, and mechanical vibration from the dump truck units.